Estimação de parâmetros de competição entre clones de eucalipto - Moura, Gustavo Paes Leme de (2009)
The objective of this study was to compare self and non-self-competition among Eucalyptus clones and to estimate parameters related to the ability of competing or tolerating competition at the plant level. To do that, six commercial clones that belong to the forestry company PLANTAR S/A were used. In August 2007, the first experiments in which the six clones were evaluated in two spacings within the row, 1.5 m or 3.0 m, with row spacing of 3.0 m were implemented in Curvelo / MG. Each clone was evaluated either exerting or suffering competition. The adopted system for each experiment was similar to a nine-hole model. The central hole had the clone suffering competition, whereas the other eight had the same clone exerting competition. Each clone suffering competition was replicated eight times. Thus, six contiguous experiments were done for each spacing. Again in Curvelo / MG and also in Felixlândia / MG other experiments with the same clones and two spacings, using a layout that was similar to the previous one, were deployed in March 2008. Twelve months after planting, the circumference at breast height and height of the plants located in the center of the nine holes was noted in all the experiments. In the experiments deployed in Curvelo, in August 2007, the same data were obtained at eighteen months. The following competition-related parameters were estimated with the mean data, using a model similar to the dialel: general competing ability (ci), competition tolerance (tj), specific competing ability (sij) and performance per se of the clone (aj). The average performance of clones in self-competition was similar to non-self-competition; so, there was no wood productivity loss at first. The clones differed in their competing ability (ci), competition tolerance (tj), and performance per se (aj). No clone has shown positive and high ci and tj. Clone B showed always positive estimates of aj and ci and it has potential to be used in combination.